Large-Scale Uniform Silver Nanocave Array for Visible Light Refractive Index Sensing Using Soft UV Nanoimprint - Jinfeng Zhu; Yanqiang Bai; Lirong Zhang; Zhengyong Song; Hai Liu; Jianyang Zhou; Timothy Lin; Qing Huo Liu (IEEE Photonics Journal)
In this paper, a wafer-scale uniform silver nanocave array is fabricated by soft ultraviolet nanoimprint lithography. We investigate its plasmonic effects using far-field and near-field experimental approaches and illuminate the physics inside by theoretical analysis and computational simulation. The array shows robust multispectral features for various surrounding media and possesses the sensitivity up to 514.7 nm/RIU in the visible range, which is promising for the mass production of high-performance plasmonic refractive index sensors.